Moderating Effects of Religiosity on the Relationship between Traumatic Deployment Experiences and Suicidal Behaviours among Military Veterans in North East Nigeria - Anongo, Fredrick Sonter; Shaapera, Paul Tersoo; Okpala, Micheal Okemefuna; Ugese, Jonathan Iornenge; Mbanugo, Chrismichael Joy (Social Science Research, 2024)
Studies have shown that exposure to traumatic experiences, such as wars and other life-threatening events can increase risk of suicidal behaviors, whereas participation in religious activities and certain religious beliefs can reduce risk. However, despite the increasing rates of suicidality among Nigerian military personnel and their high affinity to religious beliefs and practices, it still remains unclear the mechanism through which religiosity operate in moderating the relationship between combat experiences and their reported suicidal behaviours. The current study examined the moderating effects of religiosity on the relationship between traumatic experiences and suicidal behaviors in 325 military personnel who were returnee combatants in the North-Eastern Nigeria. The study adopted a cross-sectional survey design and participants who met inclusion criteria were purposively sampled across three randomly selected states that make-up the North East zone. Participants responded to five standardised measures assessing combat experiences, moral injury, social support, religiosity and suicidal behaviours. Bivariate and Multivariate analyses using Pearson correlation and Hierarchical regression were utilized to test the main and moderating influence. Results indicated a strong positive association between traumatic experiences and suicidal behaviors. Likewise, moral injury correlated positively with suicidal behaviours, while religiosity was found to be inversely associated with suicidal behaviors. Result further indicated a significant interaction between religiosity and traumatic experiences in their effect on suicidal behaviors. These findings suggest that religiosity may play a role in reducing the risk of traumatic experiences-induced suicidal behaviors among military veterans and therefore recommend incorporation of psychospiritual intervention as a veritable tool for suicide control in military veterans.